Znanstveno publiciranje v slovenskem prostoru - Miholič, Petruša (Zdravniški vestnik, 2005)
Background. In the process of scientific communication information get exchanged and scientific publishing plays a dominant role. Publishing of the scientific research results is a basic characteristics of the scientific communication. Methods. We analysed publications from the period 1992-2003 in the field of biomedicine in Slovenia. We used the computerised Slovenian national bibliographz for the field of biomedical sciences Biomedicina Slovenica. Number of publications were compared to the funds earmarked by the Ministry of education, science and sport in the period 1992-2003. Results. In the targeted period the highest increase of published articles was observed with conference contributions. As far as English articles were concerned, they appeared most frequently in magazines. Articles published in congress miscellanies followed. A comparison between slovenian and english publications showed that the latter prevailed only with original scientific articles. Conclusions. Using this study, we concluded there is no prevailing correlation pattern between the number of publications and amount of funds earmarked bz the Ministry of education, science and sport for research infrastructure.
Keywords: financing; financiranje; raziskovalno delo; research work; scientific communication; scientific publication; Slovenia; Slovenija; znanstvene objave; znanstveno komuniciranje